2015
DOI: 10.1063/1.4905285
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric functions of Cu2ZnSnSe4 and Cu2SnSe3 semiconductors

Abstract: The dielectric functions of co-evaporated Cu2ZnSnSe4 (CZTSe) and Cu2SnSe3 (CTSe) polycrystalline layers are determined accurately from self-consistent spectroscopic ellipsometry analyses. To minimize the effects of the compositional modulation and light scattering induced by rough surfaces, quite thin CZTSe and CTSe layers (<50 nm) having the single-phase stoichiometric compositions are characterized. The dielectric functions of CZTSe and CTSe show rather similar spectral features with almost identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 74 publications
5
29
1
Order By: Relevance
“…this study is smaller than that of as-grown CTSe (~0.84 eV) in our previous study [12,15]. Recently, it was also reported that the bandgap of CTSe thin films decreases from 0.68 to 0.49 eV as the growth temperature increases from 370 to 455°C [17,18]. The discrepancy in the optical bandgap between the as-grown and annealed samples may be ascribed to the band tail, which has been correlated to the poor crystallinity of films [19].…”
Section: Introductioncontrasting
confidence: 60%
“…this study is smaller than that of as-grown CTSe (~0.84 eV) in our previous study [12,15]. Recently, it was also reported that the bandgap of CTSe thin films decreases from 0.68 to 0.49 eV as the growth temperature increases from 370 to 455°C [17,18]. The discrepancy in the optical bandgap between the as-grown and annealed samples may be ascribed to the band tail, which has been correlated to the poor crystallinity of films [19].…”
Section: Introductioncontrasting
confidence: 60%
“…On the other hand, in an attempt to explain the wide range of E G values for this compound reported, it has been suggested that values of E G higher than about 0.60 eV could be explained as due to the Burstein–Moss shift effect observed for degenerated semiconductors. In such a case, the band‐gap energy due to this effect is given by the expression EGBM(p>pnormaldeg)=EGnd+(2/8mnormalh*)(3p/π)2/3, where p deg is the critical hole concentration for which the semiconductor becomes degenerate, E Gnd the band‐gap energy for the non‐degenerate semiconductor and (ℏ 2 /8 m h *)(3 p /π) 2/3 the Burstein–Moss shift term.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, although it has been established that stoichiometric Cu 2 SnSe 3 crystallizes in a monoclinic structure at low and in a cubic structure at elevated temperatures; much of the bulk materials , films , and nanocrystals crystallize in a cubic or wurtzite structures at room temperature. On the other hand, while first‐principles calculations and ellipsometry studies determine for Cu 2 SnSe 3 a band‐gap energy at room temperature from 0 to 0.45 and 0.49 to 0.68 eV, respectively, a considerable larger value of E G ranging from 0.5 to 1.7 eV was found from absorption spectra .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The interaction between the Cu-3d orbitals and Se-4p orbitals pushes the valance band position to higher energy levels which gives rise to the reduction in the effective E g Ref. [29]. Therefore, decreasing Cu content in the CZTSe thin films leads to weaker interaction of CueSe, and thus higher band gap value.…”
mentioning
confidence: 99%